Meningkatkan Kemampuan Mengenal Konsep Bilangan Anak Usia 4-5 Tahun Dengan Bermain Kartu Domino di TK Ar-Rasyid Batam - Solikah Solikah; Fitria Mareta Sari; Devi Arisandi (LPPI Yayasan Almahmudi bin Dahlan, 2023)
Understanding numbers is not only important in an academic context, but is also important in children's daily lives. This ability provides a solid foundation for children to solve problems, think critically, and make better decisions in various situations in their future lives. The aim of this research is to determine the application of playing domino cards to improve the ability to recognize number concepts in children aged 4-5 years at Ar-Rasyid Kindergarten Batam. The type of research is Classroom Action Research which is a strategic way for educators to improve and improve educational services in the context of classroom learning. The results of the research were that in cycle 1, 45% of children were in the Not Yet Developed category and in cycle II it was only 15% of 20 children. Furthermore, in cycle 1, 20% of children were in the Starting to Develop category, while in cycle II it was only 5%, which means that many children were familiar with the concept of numbers as a learning objective. Switching to the Developing According to Expectations category in cycle 1, 25% of children were in this category, whereas after cycle II it increased to 55%. Finally, in the Very Well Developed category in cycle 1 it was only 10%, whereas after cycle II it increased to 25%. The increase in the average ability to recognize number concepts for children aged 4-5 years is good, so the classroom action research is considered complete, because it has achieved indicators of success. The implication of the research results is that children will more easily accept information or learning if the teacher presents it in the form of learning and teaching activities that are fun and interesting for them. Keywords: Concept of Numbers, Domino Cards, ECE